Perfil sérico de citocinas e seu desempenho na avaliação da inflamação e fibrose hepática em pacientes com hepatopatia crônica - Osvaldo Flavio de Melo Couto (2015)
Background & Aims: the pathogenesis of chronic liver diseases is not fully understood. It involves hepatocellular inflammation and death ruled by a microenvironment of cytokines and chemokines interactions. The characteristics of the expression of these biomarkers are important to further elucidate the pathogenic mechanisms of the hepatic disorders. We aimed to investigate the cytokines and chemokines serum profile ofpatients with chronic liver disease (CLD) of different etiologies and determine the accuracy of these biomarkers serum levels in the diagnosis of hepatic inflammation and fibrosis. In addition, we evaluated the performance of the serum concentrations of hyaluronic acid (HA), collagen-IV and the aspartate aminotransferase to platelet ratioindex (APRI) in the diagnosis of fibrosis. Methods: the study included 225 consecutive adult patients with CLD with indication for a liver biopsy and 15 healthy individuals to serve as a control group. Interleukin (IL)-1, IL-2, IL-4, IL-5, IL-6, IL-10, IL-12p70, tumor necrosis factor-, interferon (INF)-, CCL2, CCL5, CXCL8, CXCL9 and CXCL10 were measured in the serum by cytometric bead array. The median serum levels, radarcharts and correlation networks were used to study the cytokines/chemokines profile. The areas under the receiver operating characteristic curves (AUROC) were calculated in order to determine their performance for the diagnosis of inflammation and fibrosis.Logistic regression was used to study the relation between the biomarkers and the different etiologies of liver disease and hepatic fibrosis. Results: serum levels of all biomarkers were significantly higher in the patients with liver disease when compared to the healthy controls. Cytokines and chemokines profile was somewhat different according to the etiology. The logistic regression demonstrated CXCL10 and CCL2 assignificant biomarkers of chronic viral hepatitis, when compared to the non-alcoholic fat liver disease (NAFLD) and autoimmune diseases (AI) patients, respectively. CXCL8 was more commonly associated with NAFLD and AI when compared to chronic virus hepatitis. CXCL10 correlated positively with the grade of inflammation and presented agood performance for the diagnosis of liver inflammation in the group of patients with CLD. CCL2 presented negative correlation with the grade of inflammation and fibrosis stages. When the patients were separated into groups according to the etiology of the liver disease, INF-, and CXCL10 presented a relatively good performance for the diagnosis of inflammation in chronic viral hepatitis, and IL-5 and CXCL8 in the cryptogenic group. CCL2 correlated negatively with the grade of inflammation in the groups of chronic viral hepatitis, AI and cryptogenic, and presented a relatively good performance for the diagnosis of lack of inflammation in these groups. None of the evaluated cytokines/chemokines performed better than the aminotransferases in the diagnosis of hepatic inflammation. The serum markers with best performance for fibrosis staging were HA, Collagen-IV and APRI. CCL2 and CXCL-10 presented a relatively good performance for the diagnosis of fibrosis and CCL2 correlated negatively with fibrosisstage. Conclusions: cytokines and chemokines profile was different according to the etiology of the CLD. CXCL10, CCL2 and CXCL8 were associated with specific etiologic groups. CCL2 and CXCL10 are important biomarkers for the diagnosis of inflammation and fibrosis. CXCL10 correlated with the presence of inflammation and fibrosis andCCL2 correlated with the absence of both types of lesion. IL-4, IL-10, INF-, CXCL-9 deserve further investigation to confirm or refute their usefulness in specific situations.